AgOTf-catalyzed reaction of sulfonyl hydrazones with ynamides led to stereoselective synthesis of α-amino alkenyl-substituted hydrazone derivatives. Issue 39 (27th September 2019) - Cao, Ziping; Yan, Shikun; Zhao, Changyin; Sun, Xuejun; Tian, Laijin; Meng, Xin
Abstract: A novel method for the synthesis of α -amino alkenyl-substituted hydrazone derivatives was disclosed through silver-catalyzed reaction of sulfonyl hydrazones with ynamides. The present method features mild conditions, high stereoselectivity and good yields. The proposed mechanism involves silver-mediated generation of a keteniminium ion intermediate to facilitate the stereoselective addition of hydrazones in the presence of K2 CO3, while pyrazole ring could not be constructed under the current conditions. Graphical abstract: Image 1 Highlights: Synthesis of α -amino alkenyl-substituted hydrazone derivatives was achieved in high efficiency. The reaction could proceed in a highly stereoselective manner. This work achieved the alkenylation of NH of hydrazones that was often ignored.